2018
DOI: 10.13080/z-a.2018.105.014
|View full text |Cite
|
Sign up to set email alerts
|

Grain morphology, texture and colour-related compounds of bread wheat cultivars in relation to cultivation regimes and growing location

Abstract: Digital wheat grain classification systems are primarily based on kernel image and texture features. These traits are highly environment-dependent, so sample-to-sample variation may affect results of grain classification, grading, or discrimination. The main aim of this study was to determine the intra-cultivar variation of wheat kernel size, shape, colour, endosperm hardness and selected chemical compounds (carotenoids, phlobaphenes and proteins) associated with kernel colour. In the study, four winter bread … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Tańska et al [52] reported that variation in grain color of wheat was reflected by changes in its chemical composition but not the environment which is in partial agreement with the results of our study. In addition, the accumulation of carotenoids and anthocyanins pigments in wheat grain accounted for the large variation in its grain color [52][53][54][55] and may have played a role in the grain color differences for the single variety of teff sampled across multiple locations in our study. Overall, the average of 63.5% of the variation in grain color can be attributed to the variation in the soil physicochemical properties that influenced several parameters that were correlated with grain color in this study (Table 5).…”
Section: Discussionsupporting
confidence: 93%
“…Tańska et al [52] reported that variation in grain color of wheat was reflected by changes in its chemical composition but not the environment which is in partial agreement with the results of our study. In addition, the accumulation of carotenoids and anthocyanins pigments in wheat grain accounted for the large variation in its grain color [52][53][54][55] and may have played a role in the grain color differences for the single variety of teff sampled across multiple locations in our study. Overall, the average of 63.5% of the variation in grain color can be attributed to the variation in the soil physicochemical properties that influenced several parameters that were correlated with grain color in this study (Table 5).…”
Section: Discussionsupporting
confidence: 93%
“…The grain width, unproductive water use, grain area size, and grain volume showed maximum load for this PC indicating that these were the most variable traits. However, Tańska et al (2018) pointed out that the seed dimensions and shape were constant among the cultivars with highest variation shown by grain thickness and grain volume. The highest values for grain width, unproductive water use, grain size and grain volume indicated a positive correlation among these traits.…”
Section: Discussionmentioning
confidence: 98%
“…The grain size, shape and color variation have economic implications in bread wheat. These are the primary physical features that determine the market value of grain (Tańska et al 2018). The grain size is positively correlated with specific grain weight, a trait related to the efficiency of wheat transport and storage of photosynthates (Clarke et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Horvath and Veha [70] investigated the dependence of wheat grain color characteristics on the grain size. Tanska et al [71] investigated wheat grain color in relation to the cultivation regime.…”
Section: Wheat Grain Surface Color Propertiesmentioning
confidence: 99%